THE RISE OF QATAR AS A SOFT POWER AND THE CHALLENGES - Antwi-Boateng, Osman (European Scientific Journal, ESJ, 2013)
This paper argues that Qatar exercises soft power influence in a troubled region via attraction and “carrots”. The sources of attraction includes: Qatar’s political stability derived from its military alliance with the U.S and effective income redistribution policies and a progressive higher education system which have greatly enhanced the stature of Qatar in the Middle East. Qatar offers the following “carrots” for influence: the potency of its Aljazeera Network, “carrot diplomacy”, sports investments and a generous foreign aid policy. However, the efficacy of these tools could be undermined, by the lack of a democratic culture in Qatar, questionable associations and causes, the unsustainable trajectory of “carrot” diplomacy and a creeping shift towards hard power in resolving conflicts and its attendant backlash.